Gaming-Based Tele-Exercise Program to Improve Physical Function in Frail Older Adults: Feasibility Randomized Controlled Trial - Lakshmi Kannan; Upasana Sahu; Savitha Subramaniam; Neha Mehta; Tanjeev Kaur; Susan Hughes; Tanvi Bhatt (JMIR Publications, 2024)
BackgroundFrailty leads to reduced physical activity can cause increased fall risk. This contributes to accelerated aging processes, leading to adverse health outcomes and reduced quality of life. We have developed and piloted the design, usability, safety, and feasibility of a gaming-based cognitive-motor (CogXergaming) tele-exercise protocol in prefrail older adults. ObjectiveThis pilot randomized control trial tested preliminary feasibility and effectiveness of the CogXergaming telehealth protocol for improving physical function. MethodsCommunity-dwelling, prefrail older adults were randomly assigned to CogXergaming (n=13) or a control group (n=14). The CogXergaming group received supervised tele-exercises in a gaming format for 6 weeks (3 sessions per week) comprising 18 sessions lasting 90 minutes each. Control group participants participated in a Matter of Balance (MOB), an 8-week, once-a-week structured 90-minute tele-session that has been shown to reduce the fear of falling and increase physical activity. Feasibility of training was obtained by computing the median duration of training sessions for the CogXergaming group. Effectiveness was assessed using dynamic balance control (Four Square Step Test), subjective self-efficacy (Activities-Specific Balance Confidence scale), gait function (Tinetti Performance Oriented Mobility Assessment), muscle strength (30-second chair stand test), and endurance (2-minute step in-place test). ResultsOf the 45 participants enrolled in the study, 4 participants from CogXergaming group and 5 from MOB group lost contact after signing the consent form and did not receive their respective intervention. Eighteen participants were randomized to each group. In the CogXergaming group, 15 (83%) completed the intervention, with 3 (16%) dropping out in the first week. In the MOB group, 16 (88%) completed the program, with 2 (11%) withdrawing during the first week. In addition, there was a significant time group interaction for Four Square Step Test (F1,21=5.55, P=.03), Tinetti Performance Oriented Mobility Assessment (F1,25=4.16, P=.05), and 30-second chair stand test (F1,21=5.06, P=.03), with a significant improvement in these measures for the CogXergaming group post training, compared with no change observed in the MOB group. ConclusionsThese pilot findings indicate that CogXergaming is feasible and applicable in prefrail older adults. Such game-based protocols can be beneficial in improving physical function among community-dwelling, prefrail older adults, however, the efficacy of such training requires further investigation. Trial RegistrationClinicalTrials.gov NCT04534686; https://clinicaltrials.gov/study/NCT04534686